ANALISIS PENGARUH PELAKSANAAN GERMAS TERHADAP KESEHATAN LANSIA - Agustini Lase; Mappeaty Nyorong; Asriwati Asriwati (Jurnal Keperawatan Priority, 2022)
The low implementation of GERMAS in 2020 has a major impact on their health, namely the increased morbidity rate in the elderly. This study aims to analyze the effect of the implementation of GERMAS on the health of the elderly in the working. This study used a quantitative analytical survey with a cross-sectional. The location in the work area of ​​Ulunoyo Health Center, South Nias Regency. The research population consisted of 216 elderly people, samples in this study was 68 people. The technique used is purposive sampling. Data were analyzed using the chi-square test and logistic regression. The results showed that there was an effect of physical activity on the health of the elderly, and an influence of the culture of fruit and vegetable consumption on the health of the elderly who participated. There was an effect of smoking on the health of the elderly, an effect of not consuming alcoholic drinks on the health of the elderly, an effect of conducting regular health checks on the health of the elderly, an effect of maintaining environmental cleanliness on the health of the elderly, an effect of using a latrine on the health of the elderly. The variable that had the most influence on the health of the elderly who participated was the variable of conducting regular health checks. Based on the results of the research, it is suggested that Health Center should be more active and improve special health services for the elderly.